Caracterização e comparação de genótipos de frutos umbuzeiro (Spondias tuberosa Arruda Câmara) do sudoeste baiano - Moreira, Marcílio Nunes (2022)
The umbu tree, a plant belonging to the Spondias genus and Anacardiaceae family, has 18 species that are located in the Americas, Asia and Oceania. The fruit can be consumed fresh or processed into several other products. With Brazilian production estimated at 7765 t in 2018 and Bahia as the largest producer of these fruits, accounting for 5752 t of the total produced, this fruit was responsible for moving approximately 8,260,000.00 reais in 2018. Therefore, the present work aims to analyze bioactives and antioxidants from different genotypes of umbu (Spondias tuberosa Arruda Câmara) from southwestern Bahia and compare them.The following analyses were carried out: acidity index, pH, soluble solids, water activity, ash, color, lipids, proteins and moisture according to the methodology of Instituto Adolfo Lutz (IAL, 2008). Bioactive compounds (phenolics, total flavonoids, total carotenoids) were analyzed according to the specific methodology for fruits and the determination of antioxidant capacity was performed by the ABTS+• radical capture method, DPPH• free radical scavenging activity, ferric reducing antioxidant potential (FRAP) and oxygen radical absorption capacity (ORAC), which were determined by spectrophotometry. The identification and quantification of volatile compounds was performed by a gas chromatograph (GC) coupled to a mass spectrometer (MS). The results obtained were statistically treated with SAS software. Among the 13 genotypes analyzed, BGU44, BGU45, BGU61, BGU75 and EPAMIG01 stood out with more than 50g of fruit mass. The BGU 61 genotype had the highest moisture content, AT (% citric acid) and the highest amount of ash while BGU44 had the highest ºBrix and the highest pH value. All varieties had high Aw with no significant difference between them. The BGU45 genotype stood out, obtaining greater amounts of total phenolic compounds (32.15 mg EAG/100g) and total flavonoids (0.88 mg Quercetina/100g) and EPAMIG01 was found to be 35.3288 (µg of β-carotene/g of pulp) being the largest amount among the analyzed genotypes. The BGU45 and BGU44 genotypes obtained the best results for antioxidant activity by the ABTS+•, DPPH•, FRAP and ORAC assays. Specific volatile compounds were found in the genotypes BGU45 (butyl acetate and humulene), BGU61 (γ-muurolene, β-selinene, 3,7(11)-selinadiene, valencene and γ-selinene) and BGU75 (methyl hexanoate, 4-pentenyl butyrate), 1-hexanol, 1-octen-3-ol). It is concluded that among the 13 genotypes studied, the genotypes EPAMIG01 and BGU75 showed promise for industrialization and fresh consumption due to their size and pulp yield, genotypes BGU44 and BGU45 stood out in their antioxidant capacity and the genotypes BGU45, BGU61 and BGU75 for presenting specific volatile compounds among the 5 that were studied